Oscillations in pedunculopontine nucleus in Parkinson’s disease and its relationship with deep brain stimulation - Li, Min; Zhang, Wangming (Frontiers in Neural Circuits, 2015)
The recent development of deep brain stimulation (DBS) of the pedunculopontine nucleus (PPN) for the treatment of parkinsonian patients, particularly those in advanced stages with axial symptoms, has ignited interest into the study of this brain nucleus. In contrast to the extensively studied alterations of neural activity that occur in the basal ganglia in Parkinson’s disease (PD), our understanding of the activity of the PPN remains insufficient. In recent years, however, a series of studies recording oscillatory activity in the PPN of parkinsonian patients have made important findings. Here, we briefly review recent studies that explore the different kinds of oscillations observed in the PPN of parkinsonian patients, and how they underlie the pathophysiology of PD and the efficacy of PPN DBS in these disorders.